PENGEMBANGAN MEDIA PEMBELAJARAN MOBILE LEARNING "NUMET" UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA SEKOLAH DASAR - Reza Muhamad Zaenal; Oman Suryaman; Atang Sutisna (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Numerical ability is an ability that is measured in the Minimum Competency Assessment. If we look at the results of PISA, the numeracy skills of Indonesian students are still at a low level compared to other countries. These problems need to find a solution if we want to improve the quality of our education. Learning based on mobile learning applications is an alternative, where with this application students can study anywhere. Then a learning media based on Mobile Learning Numeracy will be developed called "NuMet" which is expected to help students improve their numeracy skills. The purpose of this study was to find out whether the NuMet application developed was effective and practical in helping students improve their numeracy skills. The research method used in this research is the Research and Development (R&D) ADDIE model. Then, to find out the effectiveness of NuMet, it was analyzed by using the Paired Sample t-Test. The Numet product developed was declared valid by experts, then the NuMet application was effective in improving elementary school students' mathematical numeracy skills, this can be seen from the sig (2-tailed) value of 0.000 <0.05. As for practicality, the average practicality score is 75.67, so the developed NuMet is practical with good criteria. The implication of this research is that the results of developing the NuMet application can assist teachers in improving students' numeracy skills in order to face the minimum competency assessment.